Atomic Coordination Reflects Peptide Immunogenicity - Antipas, Georgios S. E.; Germenis, Anastasios E. (Frontiers in Molecular Biosciences, 2016)
We demonstrated that the immunological identity of variant peptides may be accurately predicted on the basis of atomic coordination of both unprotonated and protonated tertiary structures, provided that the structure of the native peptide (index) is known. The metric which was discovered to account for this discrimination is the coordination difference between the variant and the index; we also showed that increasing coordination difference in respect to the index was correlated to a correspondingly weakening immunological outcome of the variant. Additionally, we established that this metric quickly seizes to operate beyond the peptide scale, e.g. over a coordination shell inclusive of atoms up to a distance of 7 Å away from the peptide or over the entire pMHC-TCR complex. Analysis of molecular orbital interactions over a range of formal charges further revealed that the N-terminus of the agonists was always able to sustain a stable ammonium (NH3+) group which was consistently absent in antagonists. We deem that the presence of NH3+ constitutes a secondary observable with a biological consequence, signifying a change in T cell activation. While our analysis of protonated structures relied on the quantum chemical relaxation of the H species, the results were consistent over a wide range of peptide charge and spin polarization conditions.